Health communication: A study on health policy and knowledge translation on new media platforms - Kumar, Gayathri S; Krishnan, Keerthy; C, Karthika (International Journal of Psychosocial Rehabilitation, 2020)
Health communication is a research or the application of transmitting health related knowledge such as education in health, campaigns on health and doctor patient communication. New media or social media have marked its presence in the health care sector since the beginning of this decade. Physicians and other healthcare professionals make use of online media platforms for the promotion of health communication activities. The medical applications are easily manageable and there is a possibility of anytime consultation. This research describes how social media channels are being used to encourage health communication practices among users. The most studied new media gadgets are mobile phones and smart watches. The core purpose of the study was therefore to examine the scope and effect of mobile healthcare applications on the daily lives of its users in Kerala and the research study has also identified the actual need of health-related mobile apps among Keralite. The credibility and accessibility of mobile apps related to the health care among the users were also studied to identify the recent trends in communication strategy. A quantitative research method has been used to find out the objectives of the study. A structured questionnaire with eighteen questions was distributed among 200 samples through various social media platforms. Samples were selected using purposive sampling technique. The responses received from the survey helped to identify the users of such applications with a collective set of details of users from two major cities of Kerala, Trivandrum and Kochi.